Kontribusi Mata Kuliah Kewirausahawan terhadap Minat Berwirausaha Mahasiswa PGSD FKIP USK - Nurmasyitah Nurmasyitah; Ahadin Ahadin; M Hussin Affan; Suci Herawati (Universitas Syiah Kuala, 2022)
On the basis of entrepreneurship, it really helps students to be able to grow an independent attitude after graduating from the world of lectures, where as we know that unemployment is one of the very serious problems in Indonesia, which is still difficult to reduce the unemployment rate, where there is an increase in the number of residents, the field of work is not much. increase. So it is very cool that the interest in entrepreneurship of students can grow well and high because when viewed in general the interest of the Indonesian young generation in entrepreneurship is still relatively low. Seeing this situation, it is very necessary in the education world where in the curriculum there are entrepreneurship courses, where we know that the world of education has a responsibility to increase interest in entrepreneurship of the younger generation. This study aims to determine the contribution of entrepreneurship courses to the interest in entrepreneurship of PGSD FKIP USK students.